2018
DOI: 10.1002/erv.2599
|View full text |Cite
|
Sign up to set email alerts
|

Parental characteristics in association with disordered eating in 11‐ to 12‐year‐olds: A study within the Danish National Birth Cohort

Abstract: We examined the association between parental characteristics and disordered eating among 11- to 12-year-olds within the Danish National Birth Cohort. Frequency of fasting, purging, and binge eating was obtained by self-report from 37,592 children and combined into a measure of disordered eating (no, monthly, and weekly). Information on parental characteristics was obtained during pregnancy, from the 7-year follow-up, and by linkage to population registers. Data were analysed using multinomial logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Indeed, studies of nonclinical samples of children aged 6–11 years indicate that approximately 9–14% of girls and 5–8% of boys report DEBs (Ricciardelli & McCabe, ). In a recent study of 11‐ to 12‐year‐olds, we observed that overweight co‐occurred with DEBs (Larsen, Strandberg‐Larsen, Olsen, Micali, & Nybo Andersen, ). This is in line with increasing evidence showing that childhood overweight predicts later onset of DEBs (Forrester‐Knauss, Perren, & Alsaker, ; Micali et al, ; Munkholm et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, ; Reed, Micali, Bulik, Smith, & Wade, ; Stice, Presnell, & Spangler, ; Wiklund et al, ).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Indeed, studies of nonclinical samples of children aged 6–11 years indicate that approximately 9–14% of girls and 5–8% of boys report DEBs (Ricciardelli & McCabe, ). In a recent study of 11‐ to 12‐year‐olds, we observed that overweight co‐occurred with DEBs (Larsen, Strandberg‐Larsen, Olsen, Micali, & Nybo Andersen, ). This is in line with increasing evidence showing that childhood overweight predicts later onset of DEBs (Forrester‐Knauss, Perren, & Alsaker, ; Micali et al, ; Munkholm et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer, Paxton, Hannan, Haines, & Story, ; Reed, Micali, Bulik, Smith, & Wade, ; Stice, Presnell, & Spangler, ; Wiklund et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…We had no information on weight status between age 1 and 7 years, and it is likely that overweight occurring in this period, as well as after age 7 years may increase the risk of DEBs in late childhood/early adolescence. Unfortunately, no prospectively collected weight measures from age 7 to 11 years were available, and we have previously shown that overweight at age 11 years is associated with higher risk of DEBs (Larsen et al, 2018). The definition of childhood weight status and cut-offs for overweight vary considerably.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations